Implementation of Intrusion Detection System with Rule-Based Method on Website - Firdyanto, Tri; Rushendra, Rushendra (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The aim of this research is to implement an intrusion detection system using rule-based methods on websites. The approach in this research is the development of an intrusion detection system (IDS). research results after implementation, testing, and acceptance of test results, conclusions can be drawn. The detection system can be implemented well in website-based applications using a rule-based method.